2011
DOI: 10.1371/journal.pone.0025911
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Imaging Using PET and SPECT: The Effects of Anesthetic and Carrier Gas on [64Cu]-ATSM, [99mTc]-HL91 and [18F]-FMISO Tumor Hypoxia Accumulation

Abstract: BackgroundPreclinical imaging requires anaesthesia to reduce motion-related artefacts. For direct translational relevance, anaesthesia must not significantly alter experimental outcome. This study reports on the effects of both anaesthetic and carrier gas upon the uptake of [64Cu]-CuATSM, [99mTc]-HL91 and [18F]-FMISO in a preclinical model of tumor hypoxia.Methodology/Principal FindingsThe effect of carrier gas and anaesthetic was studied in 6 groups of CaNT-bearing CBA mice using [64Cu]-CuATSM, [99mTc]-HL91 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
1
35
0
3
Order By: Relevance
“…At the time examined, the radiocopper is not localized in areas of strong hypoxia as delineated by immunohistochemistry. The decrease in tumor retention was more pronounced for 64 Cu-acetate than 64 Cu-ATSM (34). Muscle retention was unaffected by the inhaled gas.…”
Section: Correlation Between Hypoxia and Autoradiography At 15 Minutementioning
confidence: 87%
“…At the time examined, the radiocopper is not localized in areas of strong hypoxia as delineated by immunohistochemistry. The decrease in tumor retention was more pronounced for 64 Cu-acetate than 64 Cu-ATSM (34). Muscle retention was unaffected by the inhaled gas.…”
Section: Correlation Between Hypoxia and Autoradiography At 15 Minutementioning
confidence: 87%
“…Importantly, the different imaging time points and anesthetic procedures applied in the different studies complicate a direct comparison of results. It has previously been shown that both anesthetics and level of oxygen in anesthetic gas mixtures can influence tissue uptake of both 64 Cu-ATSM and copper (16,17). Therefore, to avoid fluctuations in uptake, the level of the anesthetic gas mixture was strictly kept at a constant level during all procedures from tracer injection until completion of pO 2 probe measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to avoid fluctuations in uptake, the level of the anesthetic gas mixture was strictly kept at a constant level during all procedures from tracer injection until completion of pO 2 probe measurements. However, the experimental setup has likely contributed to slower accumulation and clearance from the background than would be seen when the tracer is allowed to distribute in an unanesthetized animal (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-lived radionuclides can be used for sequential measurements, whereas radionuclides with longer half lives do Table 2 for full names. Lewis et al [133] , Yuan et al [134] , Kersemans et al [135] , Matsumoto et al [136] Ballegeer et al [137] , Bowen et al [138] , Lewis et al [133] , Myerson et al [139] , O'Donoghue et al [72] Ballegeer et al [137] , Hansen et al [140] , Matsumoto et al [136] , McCall et al [66] , O'Donoghue et al [72] , Oh et al [74] , Yuan et al [134] Grigsby et al [141] , Tateishi et al [142] , Valtorta et al [143] , Weeks et al [144] Dence et al [145] , Kersemans et al [135] , Lewis et al [146] , Matsumoto et al [136] , O'Donoghue et al [72] Dehdashti et al [86] , Lohith et al [67] , Wong et al [80] , Zhang et al [81] Chao et al [147] , Dehdashti et al [148] , Dehdashti et al [149] , Dietz et al [150] , Grassi et al [151] , Grigsby et al [141] , Kositwattanarerk et al [152] , Laforest et al [153] , Lewis et al [154] , Minagawa et al [155] , Nyflot et al [156] [ Mahy et al [158] , Mahy et al …”
Section: F]fetnim and [mentioning
confidence: 99%